Health awareness amongst adults above 40 years of age / Ruhana Zainuddin, Norshaieda Abdullah @ Adnan and Syaidatul Zarina Mat Din - Zainuddin, Ruhana; Abdullah @ Adnan, Norshaieda; Mat Din, Syaidatul Zarina (2008)
Adults above the age of forty may start to encounter problems regarding their health. This research is to determine the common diseases or ailments experienced by adults over 40. A sample of 150 respondents was gathered from three states in Malaysia. Demographic profiles such as age, gender and race were obtained and questions regarding attentiveness and awareness of health were asked. Four hypotheses were tested. Multiple regression analysis using SPSS 12.0 was employed to analyze the data. The result shows 85.8% of respondents have one or more diseases. In addition, men and women have different diseases. Moreover, different race have different disease. Furthermore, healthy lifestyle, good diet and weight management are determinants of health awareness. The results are very useful for health administrators to plan strategies to improve public health in Malaysia.